PERILAKU CYBERBULLYING DI INSTAGRAM: PERILAKU CYBERBULLYING DI INSTAGRAM - Annissah Rachmayanti; Yuli Candrasari (Linimasa : Jurnal Ilmu Komunikasi, 2022)
According to (Holmes, 2012:383) social media is part of a technology that is outrageous, where various pros and cons are easier to occur in it without being limited by time, because there is no reach in creating interactions in it, as is the case with the presence of new media Instagram in recent times. used not only as a marketing tool but also as a non-binding exchange of information and communication, but the freedom to use Instagram social media is currently being misused as a medium to launch cyberbullying actions. The purpose of this study is to find out how cyberbullying behavior on social media is against Nissa Sabyan in comments on @lambe_turah and @nissa_sabyan account posts by using qualitative content analysis methods with data collection techniques in the form of observation and data archiving in the form of categorization of uploads and comments through computer mediated communication techniques. (CMC) and taking the type of cyberbullying behavior through the aspects of cyberbullying owned by Price and Dalgleish (2010). The results of the analysis carried out found that the number of comments that came out on the posting of the account above was a form of cyberbullying behavior that showed a called name, threatened physical harm and a slammed opinion that led to the victim, based on data that the authors found the majority of account owners who carried out this behavior. female cyberbullying. Keywords— Social Media, Instagram, Cyberbullying Behavior